Kinematics and electromyography of landing preparation in vertical stop-jump - Chappell, J. D.; Creighton, R. A.; Giuliani, C.; Yu, B.; Garrett, W. E. (The American Journal of Sports Medicine, 2007)
Biomechanical analysis of stop-jump tasks has demonstrated gender differences during landing and a potential increase in risk of noncontact anterior cruciate ligament injury for female athletes. Analysis of landing preparation could advance our understanding of neuromuscular control in movement patterns and be applied to the development of prevention strategies for noncontact anterior cruciate ligament injury.